Packing and Characterizing High- power Laser Diode - Anh, Nguyen Tuan; Decoster, Didier; Huong, Au Thi (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: In the manufacturing processes of high-power laser diode modules, the module packaging technologies play an important role; decide the efficiency of the electro-optical conversation, the beam quality and the lifetime. This paper presents the packaging of high-power laser diode modules from single chip, evaluating the electro-optical characteristics and the beam quality of the modules. The obtained results show that the packaged module has an output optical power of 5 W at current 5.9 A; the Operation Voltage is 1.7 V; the Threshold Current is 1,0 A;  the Divergence Angle Mean is 36.8 degree and the Asymmetry is 1.04. These parameters are almost the same that of some on-stock modules. Thus, the application of the packaged module in social – economics is possible. Keywords: Laser diode, fiber – coupled, die bond technology; wire bond technology; electro-optical conversation efficiency, PVI characteristics, beam quality, Divergence Angle, Asymmetry.